Analysis of lncRNA Expression in Patients With Eosinophilic and Neutrophilic Asthma Focusing on LNC_000127 - Zhu, Yujin; Mao, Dan; Gao, Wei; Han, Guojing; Hu, Hong (Frontiers in Genetics, 2019)
Long non-coding RNA (lncRNA) is known to be important in many diseases. There have been some reports that lncRNA take part in the pathogenesis of systemic inflammation of asthma. LncRNA regulates gene transcription, protein expression and epigenetic regulation. However, lncRNA associated with differently airway phenotype such as eosinophilic(Eos) and neutrophilic（Neu）asthma remains unknown. We aimed at identifying the differences in circulating lncRNA signature in Eos and Neu samples. LncRNA expression was studied between blood samples from Eos patients, Neu patients and healthy individuals (Control). Bioinformatic analysis was used to describe relevant biological pathways. Using quantitative real-time PCR, lncRNA expression was measured. Finally, a novel lncRNA, LNC_000127, was inhibited by transfection of jurkat cell with lentiviral transfer, and the effect was examined by Human Asthma RT2 ProfilerTM PCR Array and western blot. Comparing with Control samples, Eos sample has 190 own lncRNA and Neu sample has 166 own lncRNA (difference ≥ 2-fold). KEGG pathway annotation data and GO terms revealed that several lncRNAs are possibly associated with respective phenotype. LncRNA was identifying to differ significantly between Eos and Neu samples by qRT-PCR. LNC_000127 was found in Eos samples, and the expression is increased in jurkat cell with the stimulation of PMA/CD28. Subsequent studies demonstrated the possibility of LNC_000127 in Th2 inflammation pathway. The results show us that lncRNA may be involved in different phenotypes of asthma. Whether we can recognize different phenotypes of asthma through these lncRNA (as biomarkers) needs further study. Targeting LNC_000127 might be effective in reducing Th2 inflammation in asthma.